1972
DOI: 10.1515/znb-1972-0912
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Studies of Flavoquinone-Metal Complexes

Abstract: Flavoquinone-metal complexesA detailed magnetic resonance investigation of the metal ion interaction with flavoquinones has been carried out with the purpose of obtaining the stoichiometry, stability and (sub) molecular structure of the complexes. The isotropic shifts of the paramagnetic chelates are analysed in terms of contact and pseudocontact contribution. It is shown that the flavoquinone-metal binding is mainly of o-type regardless of the nature of the ion.Flavoquinone-metal complexes with mono-and bival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Various properties of metal-flavin complexes were extensively investigated in solution. 8,[10][11][12][13][14][15] Here, the complexation with metals has an important influence on the electronic and redox properties of the flavin, which is signalled by large shifts in the absorption spectra. 11 However, the considerable influence of the solvent and counter ions in these studies is not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Various properties of metal-flavin complexes were extensively investigated in solution. 8,[10][11][12][13][14][15] Here, the complexation with metals has an important influence on the electronic and redox properties of the flavin, which is signalled by large shifts in the absorption spectra. 11 However, the considerable influence of the solvent and counter ions in these studies is not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, the two-step oxidation of the flavohydroquinone by ferric ions showed that flavine dismutation may occur after formation of the flavosemiquinone, providing an indirect pathway for the second oxidation step. We already proposed (Lauterwein et al, 1972) a scheme for electron transfer in biological chains, providing a link between twoelectron carriers such as NAD+ or NADP and one-electron carriers such as the heme or iron-sulfur. Following this scheme, flavohydroquinone should be the electron donor and the flavine dismutation, which can be controlled by sterical factors and acidic-basic reactions should then provide the pathway for complete oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The protons in positions 6 through 10 were again assigned for lumiflavin and its 9-bromo-and 9-deutero-and 6,9-dideuteroderivatives (4,5 between isoalloxyazine rings of neighboring FAD molecules (6,7). In 1972, a brief account of the 'H nrnr spectra was published of tetraacetylriboflavine (R, = H ; R, = R, = CH,; R,, = CH2(CHOCOCH,),CH20COCH,) and its complexes with Fez+, Co2+, Ni2+, and Cu2+ in acetone-d, (8). A full account of that work including additional information on the 'H nrnr of complexes of Cu+, Agf , Zn2 +, Cd2 +, Mn2 +, Mg2+, and Fe3+ has now been published (9,10).…”
Section: Introductionmentioning
confidence: 99%